Platform with ancient sculptures, a Nandi, and a stele with inscription - Temples of India Project Team (Jio Institute, 2024)
There is another stone platform, around a tree, in front of the entrance of the main temple where ancient sculptures of Ganesha, covered in vermilion, a Goddess, and a Nandi are kept. There is another huge sculpture of Nandi in front of the platform, facing the mandapa that displays fine craftsmanship. Ornamentation on the body of the vahana of Shiva is also rendered gracefully. There is a stone stele placed next to the platform which has an inscription engraved that belongs to a later date.